A study on indoor air pollution and its impact on health in urban field practice area: a community-based study - Sasi, Arun P.; Udgiri, Rekha S. (International Journal Of Community Medicine And Public Health, 2024)
Background: As per the 2022 World Air Quality Report, India holds the eighth position globally for air pollution, with Karnataka in South India experiencing notably poor air quality, leading to 95 deaths per 100,000 population annually. Indoor air pollution poses substantial health risks, contributing to conditions such as pneumonia, stroke, diabetes, lung cancer, and premature mortality. Methods: This study, conducted from April to July 2023 in the urban area of UHTC, Chandabowdi, aimed to assess indoor air pollution’s impact. Using simple and systematic random sampling, 128 household members were surveyed through in-person interviews with ethical clearance. Results: Of 128 participants, 44% reported respiratory symptoms, and 94% practiced unsanitary waste disposal. Ventilation issues affected 32.8%, while 75.8% reported neighborhood pollution. LPG was the primary fuel source for 97.7% of households, indicating significant environmental and health concerns. Conclusions: Urgent action is needed to address indoor air pollution’s health impacts. Clean technologies, improved building design, and lifestyle changes are essential to mitigate risks. Continuous monitoring and collective efforts are necessary for a healthier and sustainable future.